If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2(-5 + 6) = -36 Combine like terms: -5 + 6 = 1 6x + 2(1) = -36 Multiply 2 * 1 6x + 2 = -36 Reorder the terms: 2 + 6x = -36 Solving 2 + 6x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = -36 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = -36 + -2 6x = -36 + -2 Combine like terms: -36 + -2 = -38 6x = -38 Divide each side by '6'. x = -6.333333333 Simplifying x = -6.333333333
| 3x-1+x-19=180 | | 2a+2b=p | | 4n+9-6-3= | | X^3-6x^2=9x-54 | | 5x+7=7+x | | 12x-16=7x-3 | | 6y+4=6y-30 | | 0.23x=4.9+.3x | | (9x-5)(4x-5)= | | -3(-2x+2)=2x-18 | | 30x+(x^2+40x)+10x+35=180 | | 2p+3n=m | | x-(6/13)=4/13 | | X+4=3x-18 | | -3(2x-9)+2x=43 | | 7.50t=187.50 | | 18x+11=2(6x+2)+6x+7 | | 4.2+2.1x=6.3 | | 18÷2/3 | | 3n+2p=m | | 400/-9 | | 2x^2-9=3 | | 15/96 | | 12n^2+4n= | | 2x+10+4=-8 | | M^3y-27y= | | 8(4-2n)=-16n+16 | | 5(1+c)=6(2-c) | | 66/0.03= | | x=4.32 | | 4.05*0.2= | | 4(x-5)2x-1+3= |